2022
DOI: 10.1111/jcal.12678
|View full text |Cite
|
Sign up to set email alerts
|

Students' use of technology and their perceptions of its usefulness in higher education: International comparison

Abstract: Background:The rapid globalization along with the growing trend of openness and sharing approach enabled widespread of digital technologies all over the world. However, we can still find differences between countries in technology use and perceptions of usefulness for learning. Understanding students' use of educational technology and their perceptions of its usefulness is especially significant today, given the rapid penetration of online learning into higher education as a response to Covid-19.Objectives: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In line with the existing research which found that learning resources with local characteristics influence their adoption (Adam, 2019;Cohen et al, 2022;Farrow et al, 2015), English proficiency was also found to be a significant predictor of OER's perceived usefulness for professional development. Participants with high English proficiency tended to rate OERs' perceived usefulness higher.…”
Section: Differences In Oer Use During the Covid-19 Crisis According ...supporting
confidence: 84%
See 2 more Smart Citations
“…In line with the existing research which found that learning resources with local characteristics influence their adoption (Adam, 2019;Cohen et al, 2022;Farrow et al, 2015), English proficiency was also found to be a significant predictor of OER's perceived usefulness for professional development. Participants with high English proficiency tended to rate OERs' perceived usefulness higher.…”
Section: Differences In Oer Use During the Covid-19 Crisis According ...supporting
confidence: 84%
“…Millions of non-English speakers were found to adopt MOOCs less than English speakers, for in addition to the language barrier, the cultural perspective was not applicable to their local context (Adam, 2019). In countries in which English is not the native language, English proficiency was also found to be a factor influencing the use of online learning activities other than MOOCs (Cohen et al, 2022). One of the greatest potential strengths of MOOCs is the localisation of OER materials for different global contexts.…”
Section: Effects Of Personal Characteristics On Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they want encouraging connections with professors and fellow students via technology, as well as access to new resources and wider reading materials, implying a novel use of technology. In a recent study by Cohen et al (2022), perceived technology usefulness also differs not only across cohorts and countries, but also across official and unofficial technology tools used by learners. In truth, students extensively employ common technology in their academic studies (Rashid & Asghar, 2016), including Internet search engines to find information, audio recordings or videos about subjects/disciplines (e.g., YouTube, Vimeo), non-university provided scholarly websites to search for papers/journals, social networking sites to collaborate with other students on courses (e.g., Facebook or Twitter), and Wikipedia to find information.…”
Section: Forming the Triple-s Frameworkmentioning
confidence: 99%
“…The present research aims to fill these gaps in the literature in two main respects: first by exploring various ways students conceptualize online education and second by discussing the relationship between these conceptions and the mediating role of technology in students' learning. It is thought that the results might provide complementary information on students' perceptions of the usefulness of technology for their learning (Cohen et al, 2022) and help instructors improve the quality of their online courses so students' overall learning experience can be enhanced (Alqurashi, 2019).…”
Section: Introductionmentioning
confidence: 99%